Collaborative environment in inclusive education and professional competencies - Колесникова, Галина; Пустовалова, Наталья (Pedagogy and Psychology, 2021)
The article is devoted to the issue of organizing a collaborative educational environment in the context of inclusive education at a University. The analysis of the study of theoretical sources and practical experience allows us to conclude that there is insufficient training of teachers in the field of inclusive education, the formation of professional competencies. The authors give an essential characteristic of the concept of "collaborative environment", which is an innovative approach in the preparation of future bachelors of education on the basis of collaborative interdepartmental interaction. Collaboration means the joint solution of the task of training personnel on the basis of pedagogical interaction. The priority aspects of creating collaborative education include the use of the possibilities of combining individually-oriented teaching and communicational and educational technologies presented in various forms. Collaboration is also considered as a specific form of interaction and cooperation in the educational process of teachers and students on the example of teaching students with special educational needs according to the educational program "Musical Education".